2013
DOI: 10.1007/s12020-013-9889-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between bisphenol A and abnormal free thyroxine level in men

Abstract: Bisphenol A (BPA) is a chemical that is used in a variety of consumer products, and exposure to BPA is widespread among the general population. Recent studies have suggested that BPA may affect the thyroid and related pathways. However, human studies are still limited. The aim of this study was to determine the relationship between BPA exposure and thyroid function. We obtained survey data and blood samples from The Thai National Health Examination Survey IV 2009, a nationally representative cross-sectional su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 41 publications
3
37
0
Order By: Relevance
“…Antibodies against these xenobiotics have been demonstrated in a number of studies [11,12]. There have been studies showing that BPA acts as a thyroid receptor antagonist [13] and can increase serum free T4 [6]. In the present study, serum BPA was found to be associated with certain aspects of thyroid autoimmunity, in that there was a relationship between serum BPA and TPOAb or TgAb but not TRAb.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Antibodies against these xenobiotics have been demonstrated in a number of studies [11,12]. There have been studies showing that BPA acts as a thyroid receptor antagonist [13] and can increase serum free T4 [6]. In the present study, serum BPA was found to be associated with certain aspects of thyroid autoimmunity, in that there was a relationship between serum BPA and TPOAb or TgAb but not TRAb.…”
Section: Discussionsupporting
confidence: 53%
“…In the U.S. National Health and Nutrition Examination Survey (NHANES), BPA and triclosan were shown to be likely to negatively affect human immune function, as assessed by serum cytomegalovirus antibody and allergy or hay fever diagnosis [5]. We previously reported a negative association between serum BPA and serum thyroxine (T4) in males with positive serum thyroid antibodies [6] which is in agreement with a recent study in U.S. adults which suggested an inverse relationship between urinary BPA and total T4 [7]. Moreover, we have also demonstrated that estradiol is associated with thyroid autoimmunity in males [8].…”
Section: Introductionmentioning
confidence: 99%
“…More than forty published studies have reported low concentrations of BPA in human blood and serum samples (reviewed in [29], see also [44-63]). In spite of the relative consistency in BPA concentrations reported, these studies have been criticized that the uBPA measured in human serum could be the result of contamination and/or that BPA-G, the major metabolite found in blood, could be deconjugated by the extraction processes used [42,69-72].…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, more than three dozen studies have examined samples collected from pregnant women, non-pregnant adults, and fetal umbilical cords to evaluate the extent to which BPA may be present in blood or serum (reviewed in [11,29], see also [44-63]). Although a few studies used ELISA to measure BPA, the majority used analytical chemistry methods, and although most examined a limited number of human subjects compared to the studies examining urine, a few large studies have been published [32,64,65].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cashiers are exposed to high levels of bisphenol A (BPA), an endocrine disrupting chemical that has been linked to an increased risk of breast cancer, prostate cancer and other malignancies (44, 45). While there has been no direct link between BPA and thyroid cancer, studies have shown that BPA exposure can alter thyroid hormone levels (46, 47). However, retail salespersons refer to those who sell merchandise such as furniture, motor vehicles, appliances, or apparel to consumers (cashiers not included) according to 2010 SOC code; emission of low-frequency electromagnetic fields from jobs requiring equipment and BPA exposure from receipts may not explain these association.…”
Section: Discussionmentioning
confidence: 99%